MicroRNA Expression Detection Methods - Wang, Zhiguo. (Springer Berlin Heidelberg, 2010)
This book provides comprehensive descriptions of the innovative strategies and methodologies for detecting miRNA expression, their application in miRNA research and their potential as tools for clinical diagnosis and prognosis. It begins with the introduction of the overall concept and strategies of miRNA expression detection methods emphasizing the need of a wide variety of these methods to suit specific requirements for research and clinical examination in laboratories. In the following, each single chapter focuses on an independent, unique method of miRNA detection and is divided into five subsections: summary, introduction, protocol (including materials, instrument, reagent, and procedure), application and limitation, and reference. The development of the technique, the ideas behind it and the mechanisms underlying the method are given in the introduction of each chapter. The step-by-step protocols are detailed in the protocol section. Then, the applications and limitations of the methods are discussed. Finally, the literature citations are listed in reference section. Schematic diagrams are included where needed and appropriate for better illustrating the principle of the methodologies. In addition, flowcharts are also provided to outline the protocols for each of the miRNA expression detection methods. This book is aimed to target both researchers involved in miRNA research of any fields in universities and research institutions and medical practitioners who are interested in developing or utilizing miRNA profiling as a complementary and an alternative strategy for clinical diagnosis of human disease.